Electrochemical interaction between biodegradable ZX10 and WZ31 magnesium alloys and medical Ti6Al4V titanium alloy - Pavel N. Myagkikh; Evgeny D. Merson; Vitaly A. Poluyanov; Dmitry L. Merson; Marina E. Begun (Frontier Materials & Technologies)
Magnesium-based alloys are a modern material for the production of biodegradable (self-dissolving) surgical implants. Magnesium is a metal with the most negative electrode potential of all structural materials: −2.37 V. This means that close arrangement of implants made of magnesium, and for example, titanium alloys will lead to the occurrence of a galvanic effect, and accelerated electrochemical corrosion of magnesium. However, it is unknown how the ratio of the areas of titanium and magnesium products affects the magnitude of this effect. This work covers this issue. In the presented study, cylindrical samples of biodegradable ZX10 and WZ31 magnesium alloys were placed in physiological Ringer’s solution at a distance of 3 cm, from a sample of medical Ti6Al4V alloy of the same shape and size. During the test, the temperature of the corrosive environment was maintained at 37 °C. The series of experiments included corrosion tests lasting three days with the participation of one, two or four magnesium samples, thus the area ratios between the titanium and magnesium alloy were 1:1, 1:2 and 1:4. It was found that for both magnesium alloys, with an increase in the area ratio, the effect of electrochemical action decreases significantly, which is expressed in a decrease in the corrosion rate. At the same time, for the WZ31 alloy, the effect of the presence of Ti6Al4V on the corrosion rate is significantly weaker than for ZX10, which is explained by the presence of the LPSO phase in the alloy, as well as a more alloyed matrix and, accordingly, having a more positive electrode potential.